Unpacking Organizational Innovation Drivers in High-Performing Exporting SMEs: A Systemic Interaction of Internal and External Determinants Beyond the Endogenous–Exogenous Divide - SHURWERYIMANA , Fabrice (Revue Internationale des Sciences de Gestion, 2026)
In a demanding and uncertain international environment, high-performing exporting SMEs must continuously reinvent their organizational practices. This article offers a renewed perspective on organizational innovation by moving beyond the traditional dichotomy between endogenous and exogenous factors. Based on a qualitative study of six Moroccan SMEs in the agri-food and textile sectors, it shows that organizational innovation stems from a simultaneous, dynamic, and interdependent interaction between leadership characteristics, internal resources, strategic choices, sectoral requirements, and environmental opportunities. The leader acts as a catalyst, orchestrating organizational adjustments through a proactive reading of internal and external signals. The study highlights a systemic logic where each factor influences and is influenced by the others, within a co-evolutionary process. This integrated approach provides a deeper understanding of the transformation dynamics in exporting SMEs and offers a relevant analytical framework for researchers, practitioners, and policymakers. Organizational innovation is thus not merely a response to constraints, but a strategic lever for continuous change.